2017
DOI: 10.1007/s12630-017-0914-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose subcutaneous ketamine for postoperative pain management in Rwanda: a dose-finding study

Abstract: Adding subcutaneous ketamine to standard analgesic measures resulted in decreases in postoperative pain scores without serious side effects. These data can be used to inform a randomized controlled trial to compare subcutaneous ketamine plus standard care with placebo plus standard care for reducing postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The provision of adequate pain relief after surgery is an ethical responsibility of healthcare providers and a fundamental right of every patient [ 20 22 ]. Its importance has been emphasized during the early stages of recovery [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The provision of adequate pain relief after surgery is an ethical responsibility of healthcare providers and a fundamental right of every patient [ 20 22 ]. Its importance has been emphasized during the early stages of recovery [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in The provision of adequate pain relief after surgery is an ethical responsibility of healthcare providers and a fundamental right of every patient (25)(26)(27). Postoperative pain can have a significant effect on patient recovery by improving clinical outcomes, avoiding clinical complications, and finally saving health care resources (28).…”
Section: Association Of Outcomes With Types Of Surgery and Types Of Amentioning
confidence: 99%
“…Buvanendran et al [ 10 ] indicated that oral ketamine provided improved postoperative analgesia after amputation surgery without increased risk of adverse effects. Tuchscherer et al [ 11 ] found that adding subcutaneous ketamine to standard analgesic regime resulted in a reduction of postoperative pain scores.…”
Section: Introductionmentioning
confidence: 99%